Antifungal activity testing of curry leaf ethanol extract on the growth of Pityrosporum ovale and Candida albicans fungus - Purnama Sari, Ulwan; Reveny, Julia; Morin Sinaga, Siti (International Journal of Basic & Clinical Pharmacology, 2023)
Background: The curry leaf is an Indonesian plant commonly utilized as a spice. Curry leaves are abundant in secondary metabolites, which endow this plant with numerous advantages, including antibacterial and antifungal properties, as well as the ability to reduce blood sugar levels and blood pressure. The objective of this study is to assess the efficacy of an ethanol extract derived from curry leaves in suppressing the proliferation of Pityrosporum ovale and Candida albicans fungus. Methods: The symbiotic properties and phytochemical composition of curry leaf simplisia were examined. The antifungal efficacy of the ethanol extract derived from curry leaves was evaluated against Pityrosporum ovale and Candida albicans using the disc diffusion method. Calculate the precise values of the minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC). Results: The simplisia of curry leaf fulfills the criteria for simplisia characterization. Curry leaves possess a variety of secondary metabolite chemicals, including alkaloids, flavonoids, tannins, saponins, glycosides, steroids, and triterpenoids. The activity against the inhibition of fungal growth of Pityrosporum ovale and Candida albicans can suppress fungal growth with inhibition zone diameters measuring 6.93±0.15 mm and 7.27±0.47 mm, respectively. The minimum lethal concentration of leaf ethanol extract for Pityrosporum ovale fungi is 8.75%, resulting in a decrease of 98.25%. For Candida albicans fungi, the minimum lethal concentration is 12.5%, resulting in a reduction of 98.37%. Conclusions: The ethanol extract derived from curry leaves has the ability to hinder the proliferation of Pityrosporum ovale and Candida albicans fungus.